Delivery routes for faecal microbiota transplants: Available, anticipated and aspired. (September 2020) - Gulati, Monica; Singh, Sachin Kumar; Corrie, Leander; Kaur, Indu Pal; Chandwani, Lipika
Abstract: Fecal microbiota transplant (FMT) has seen a historic emergence in last decade with its sojourn recently entering into a chequered path, due to a few reports of infection and subsequent mortality. Though FMT has been extensively reported, there is no comprehensive report on the delivery routes available for this non-pharmacological treatment option. Safety, efficacy and cost of FMT not only depend on the quality of contents but also on the delivery route employed. A number of delivery routes are in use for conducting FMT, which include upper gastrointestinal routes (UGI) i.e. nasogastric/nasojejunal tube, endoscopy, oral capsules and lower gastrointestinal routes (LGI) like retention enema, sigmoidoscopy or colonoscopy. Capsules, both conventional as well as colon targeted have been the most commonly used formulations. Surprisingly, the success rates with conventional gastric delivery capsules and colon targeted capsules were found to be quite similar indicating the sufficiency of the inoculum size to withstand the microbial loss in the gastric milieu. Patient compliance, cost effectiveness, comfort of administration, level of invasiveness, patient's hospital admission, risk of aspiration and infections, multiplicity of administration required, recurrence rate are the main factors that seem to influence the choice for route of administration of physicians. The best route for FMT has not been established yet. Extensive studies are required to understand the interplay of route adopted, type of donor, physical nature of sample (fresh or frozen), patient compliance and cost effectiveness to design an approach for the risk free, convenient and cost-effective administration route for FMT.